SUBURBAN PASSENGER COMPLEX DOMESTIC RAILWAYS: THE NEED TO REFORM GOVERNANCE PROCESSES - D. Plotnikova (Вестник университета, 2018)
The issues of functioning of the suburban passenger railway complex, the main quantitative are considered. The qualitative indicators of railway transport are presented. The particular attention is paid to the problem of the lack of regular commuter traffic in the regions. The reforms carried out in the sphere of the passenger railway complex over the past twenty years, including the draft law on the formation of a new model of the organization of railway service to the population in suburban and long-distance communications submitted in 2018 are briefly analyzed. The results of the reform are evaluated.